The importance of consumer perception towards willingness to pay of Sarawak layered cake / Noor Ashyikin Jamali - Jamali, Noor Ashyikin (2018)
The main purpose of this study was to determine factors of customer perception towards willingness to pay for Sarawak layered cake. This research was done with reviewing and analyzing various researches in Malaysia. The findings revealed that the premiums that consumers were willing to pay vary inside Malaysian country. Consumers' knowledge and awareness about Sarawak Layered Cake differs. Some had more knowledge about Sarawak Layered cake and some were unknowledgeable about Sarawak Layered Cake. Some factors influencing consumers' willingness to purchase Sarawak Layered Cake were Service Quality and Image. Due to the importance of consumers' knowledge about Sarawak Layered Cake for purchase decisions, it is recommended to publish materials about Sarawak Layered Cake and deliver them to the families.